PENGARUH RETURN ON EQUITY, EARNING PER SHARE, DAN SALES GROWTH TERHADAP HARGA SAHAM PADA PERUSAHAAN YANG TERINDEKS LQ45 - Sartika Elfrida Naomi Situmorang; Muhammad Asrin Jazuli; Ilham Hidayah Napitupulu; Anita Putri (Jurnal Akuntansi dan Bisnis, 2026)
This research aims to empirically prove the influence of return on equity, earning per share, and sales growth on stock prices in companies indexed LQ45. The sampling technique in this research is purposive sampling method. The sample in this study consisted of 23 companies and 138 observation data from 2019 to 2024. The data collection technique used in this research is documentation techniques. The data was collected based on the annual report and audited financial statements of companies indexed LQ45, which can be accessed through the official website of the Indonesia Stock Exchange. Data were analyzed using multiple linear regression with SPSS version 25. The results of this research show that return on equity has no significant effect on stock prices, while earning per share has a positive and significant effect on stock prices. Furthermore, sales growth also does not have a significant effect on stock prices. These findings indicate that among the three fundamental factors, earning per share is the most dominant variable considered by investors in making investment decisions on LQ45-indexed companies in the Indonesia Stock Exchange.